Struktur Industri, Tingkat Produktivitas, dan Efisiensi Ekonomis dalam Pemenuhan Kebutuhan Hidup Layak (Studi Empiris Perajin Tahu Desa Kalisari, Cilongok, Banyumas Vs Perajin Tahu Desa Kalikabong, Kalimanah, Purbalingga) - Agus Arifin (EKO-REGIONAL, 2011)
The purposes of this research are to analyze the industry structure, productivity, economic efficiency, and the living standard of labor in tahu industry centre in Kalisari village, Cilongok district, Banyumas regency compare with those in Kalikabong village, Kalimanah district, Purbalingga regency. This research is to study which industry centre better. This research is conducted with qualitative and quantitative analysis that uses Herfindahl Index (HI) and Concentration Ratio (CR) analysis to analyze industry structure and concentration; output-input and regression to measure the productivity; R/C ratio to analyze economic efficiency; then income-UMK ratio and income- KHL ratio to analyze living standard of labor. The results show that: (1)Both of tahu industry centre in Kalisari and Kalikabong are perfect competition market. Industry in Kalikabong is more concentrated; (2) the productivity of labor in Kalisari is higher than in Kalikabong (3) the tahu enterprises in Kalisari more efficient than in Kalikabong (4) All of tahu enterpreneurs in Kalisari and Kalikabong are more than living standard level based on profit received, but many labors are less than living standard level based on wage received.  Keywords: industry structure, productivity, efficiency, labor, living standard